A review of heat integration system in dividing wall column for oleochemicals separation - Norul Malakiah, Sidek; Mohamad Rizza, Othman (Elsevier Ltd, 2019)
The dividing wall column (DWC) alone is exclaimed to be energy-efficient compared to typical distillation column (DC). However, as with DC, there is further potential energy saving can be made in the DWC through heat integration. This article reviews the recent developments of heat integrated DWC technologies including heat pump assisted distillation and internally heat-integrated distillation column (HIDiC) as well as its applications. Yet, none of these discoveries have been applied to oleochemicals separation. The underlying reasons other than limited familiarity and flexibility, are higher requirements on operation as well as design and controllability problems. This uncovered topic is of great interest and the existing literatures on the heat integration technology of the DWC would be beneficial in the attempt of designing and simulating the intensified heat integration DWC for oleochemical distillation.